Gambaran Kelengkapan Pengisian Partograf dalam Pemantauan Persalinan di Uptd Puskesmas Wajo Kota Baubau Tahun 2025 - Nining Frianti; Ahmad Noor; Rahma Anggraini (Jurnal Kesehatan Amanah, 2026)
Partographs are an important instrument in labor monitoring that functions to detect complications early, monitor labor progress, and support appropriate clinical decision-making. However, incomplete filling of partographs is still a problem in various health service facilities and has the potential to affect the quality of midwifery services. This study aims to find out the completeness of filling in the partograph in childbirth monitoring at the Wajo Health Center UPTD Baubau City. This study uses a quantitative method with a descriptive design. The research population is all partograph documents for the period November 2025 to March 2026 as many as 40 documents. The sampling technique used total sampling and obtained 32 documents that met the research criteria. Data were collected using an observation checklist sheet and analyzed univariately through frequency and percentage distributions. The results showed that as many as 28 documents (87.5%) had not been fully filled out and only 4 documents (12.5%) had been filled in completely. The components with the highest level of completeness were uterine contractions (100%), drugs and fluids (96.9%), and labor progress (93.8%). Meanwhile, the components of maternal information (12.5%) and maternal condition (31.3%) had the lowest level of completeness. Most of the filling of partographs at the Wajo Health Center UPTD still does not meet the completeness standards. It is necessary to strengthen supervision, training, and periodic monitoring to improve the quality of childbirth documentation and support the safety of mothers and babies